2003
DOI: 10.1116/1.1624256
|View full text |Cite
|
Sign up to set email alerts
|

Near edge x-ray absorption fine structure measurements of surface segregation in 157 nm photoresist blends

Abstract: Articles you may be interested inSurface segregation of photoresist copolymers containing polyhedral oligomeric silsesquioxanes studied by x-ray photoelectron spectroscopya)Near edge x-ray absorption fine structure measurements of the interface between bottom antireflective coatings and a model deprotected photoresist

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 5 publications
1
12
0
Order By: Relevance
“…This length scale corresponds to 1 to 2 molecular layers of the polyfluorene backbone; [25,26] surface counterion accumulation within this region would therefore still permit ion pairing. We note that strong surface segregation typically occurs in blends of nonionic polymers and aromatic small molecules, especially in photoresist/photoacid generator (PAG) blends; [27] the PAG triphenylsulfonium perfluoro-1-butanesufonate chemically resembles our PF-X counterions. Similar forces -hydrophobicity and surface tension -operating at both interfaces and balanced by electrostatic pairing are likely responsible for the result observed here.…”
mentioning
confidence: 99%
“…This length scale corresponds to 1 to 2 molecular layers of the polyfluorene backbone; [25,26] surface counterion accumulation within this region would therefore still permit ion pairing. We note that strong surface segregation typically occurs in blends of nonionic polymers and aromatic small molecules, especially in photoresist/photoacid generator (PAG) blends; [27] the PAG triphenylsulfonium perfluoro-1-butanesufonate chemically resembles our PF-X counterions. Similar forces -hydrophobicity and surface tension -operating at both interfaces and balanced by electrostatic pairing are likely responsible for the result observed here.…”
mentioning
confidence: 99%
“…This is in contrast to the known examples of PAG surface segregation and inhomogeneous distribution that have been previously reported in the literature for blended-PAG materials. 9,19 Since the PAG is bound and dispersed into the polymer chain, its ability to undergo any significant micro-phase separation or segregation is virtually eliminated. The distribution of PAG in the polymer-bound PAG and blended PAG resist films used in this work were probed to confirm this advantage.…”
Section: Resultsmentioning
confidence: 99%
“…Such blended-PAG CAR materials are known to have a number of potential problems, including low PAG solubility and thus low maximum PAG loadings, PAG aggregation and segregation that lead to non-uniform resist film composition, and photoacid diffusion that can lead to blurring of images and loss of critical dimension control. [9][10][11][12] These problems ultimately create a tradeoff between achieving the desired characteristics of high resolution, high sensitivity, and low line edge roughness through formulation changes to blended-PAG CAR systems (see Figure 1) and expose the main challenge for resist materials design for the next generation lithography. [13][14][15] Methods for designing resist materials that can achieve all three characteristics (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…These results are presumably due to the segregation of the copolymer Resin 1 to the air interface. Among Resins (3)(4)(5), Resin 5 that contains the most hydrophobic Monomer C, has been shown to have a higher water contact angles (static and receding angle) than Resin 3 and 4. It is expected that hydrophobicity of polymers correlates with the contact angles.…”
Section: Water Contact Angle Measurement Of Blend Filmsmentioning
confidence: 98%
“…Work by the Jablonski group demonstrated that polymer blend constituents having different hydrophobicity or surface tension, the more hydrophobic or lower surface tension species would typically wet the blend film surface when heated in air. 4 Work by the Irie group at TOK demonstrated that fluorine localized at the film surface for the blended polymer, in contrast to the uniform distribution for the fluorine-incorporated polymer. 5 The addition of the fluorine material is advantageous for altering the surface of the resist films.…”
Section: Introductionmentioning
confidence: 94%